Analysis and evaluation of erosion and deposition processes in Dong Tranh estuary (Can Gio district, Ho Chi Minh city) - Thanh, Nguyen Tien; Phuoc, Vo Luong Hong (Vietnam Journal of Marine Science and Technology, 2019)
Study site is a part of Can Gio mangrove biosphere reserve in Can Gio district, Ho Chi Minh City. At present, this area is eroded strongly due to the effects of hydrodynamic impact. Based on the field measurements of coastal profile and shoreline changes from 2013 to 2017 and combination of remote sensing method and GENESIS model, the erosion and deposition processes in 5 years are evaluated and analyzed. The results show that the study site keeps eroding over time and trend to continue in the future. Moreover the study also shows that the erosion rate in the northeast monsoon is higher than that in the southwest monsoon. These results are very important in contribution to shoreline change studies.